Structural and metabolic brain abnormalities in COVID-19 patients with sudden loss of smell. - Niesen, Maxime; Trotta, Nicola; Noel, Antoine; Coolen, Tim; Fayad, Georges; Leurkin-Sterk, Gil; Delpierre, Isabelle; Henrard, Sophie; Sadeghi, Niloufar; Goffard, Jean-Christophe; Goldman, Serge; De Tiège, Xavier (European Journal of Nuclear Medicine & Molecular Imaging, 2021)
Objectives: Sudden loss of smell is a very common symptom of coronavirus disease 19 (COVID-19). This study characterizes the structural and metabolic cerebral correlates of dysosmia in patients with COVID-19. Methods: Structural brain magnetic resonance imaging (MRI) and positron emission tomography with [18F]-fluorodeoxyglucose (FDG-PET) were prospectively acquired simultaneously on a hybrid PET-MR in 12 patients (2 males, 10 females, mean age: 42.6 years, age range: 23–60 years) with sudden dysosmia and positive detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on nasopharyngeal swab specimens. FDG-PET data were analyzed using a voxel-based approach and compared with that of a group of healthy subjects. Results: Bilateral blocking of the olfactory cleft was observed in six patients, while subtle olfactory bulb asymmetry was found in three patients. No MRI signal abnormality downstream of the olfactory tract was observed. Decrease or increase in glucose metabolism abnormalities was observed (p <.001 uncorrected, k ≥ 50 voxels) in core olfactory and high-order neocortical areas. A modulation of regional cerebral glucose metabolism by the severity and the duration of COVID-19-related dysosmia was disclosed using correlation analyses. Conclusions: This PET-MR study suggests that sudden loss of smell in COVID-19 is not related to central involvement due to SARS-CoV-2 neuroinvasiveness. Loss of smell is associated with subtle cerebral metabolic changes in core olfactory and high-order cortical areas likely related to combined processes of deafferentation and active functional reorganization secondary to the lack of olfactory stimulation.